2015
DOI: 10.1186/s12864-015-1323-9
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of Pseudoplusia includens single nucleopolyhedrovirus and an analysis of p26 gene evolution in the baculoviruses

Abstract: BackgroundPseudoplusia includens single nucleopolyhedrovirus (PsinSNPV-IE) is a baculovirus recently identified in our laboratory, with high pathogenicity to the soybean looper, Chrysodeixis includens (Lepidoptera: Noctuidae) (Walker, 1858). In Brazil, the C. includens caterpillar is an emerging pest and has caused significant losses in soybean and cotton crops. The PsinSNPV genome was determined and the phylogeny of the p26 gene within the family Baculoviridae was investigated.ResultsThe complete genome of Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 69 publications
(82 reference statements)
0
23
0
Order By: Relevance
“…The isolates showed high nucleotide sequence identity with both ChinNPV-IC and ChinNPV-ID sharing 96.4% identity and ChinNPV-IF and ChinNPV-IG sharing 99.4% identity with the PsinSNPV-IE genome (7) (GenBank: KJ631622), representative isolate of the species.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The isolates showed high nucleotide sequence identity with both ChinNPV-IC and ChinNPV-ID sharing 96.4% identity and ChinNPV-IF and ChinNPV-IG sharing 99.4% identity with the PsinSNPV-IE genome (7) (GenBank: KJ631622), representative isolate of the species.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Baculovirus species have been described using restriction endonuclease digestion profile and Sanger sequencing, and more recently by Next Generation Sequencing (NGS) [10,11,16,17,23,26,27,28,29]. Previous research has shown that HaSNPV and HzSNPV share sequence similarity of up to 99.9%, but could be distinguished by a small number of nucleotide substitutions and by open reading frame (ORF) insertions and deletions in the published consensus genome [17,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…of the family Baculoviridae that has Pseudoplusia includens single nucleopolyhedrovirus-IE (PsinNPV-IE; GenBank accession number KJ631622) as its representative isolate (1,2). We report here the complete genome sequences of seven new isolates of this species, originally obtained from infected Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) larvae collected on soybeans and cotton in the states of Minas Gerais and Mato Grosso, Brazil.…”
mentioning
confidence: 99%